Fatigue Cyclic Tests on Artificially Cemented Soil - A. Viana da Fonseca (2013)
Artificially cemented soils are frequently used in the infrastructural layers of road or railway platforms but the durability of these structures is often questioned when subjected to cyclic loads. In order to evaluate the fatigue behavior, this paper presents long cyclic triaxial tests over several soil cement mixtures using a very well graded silty sand and Portland cement In undrained cemented tests, pore pressure decreased as a sign of plastic degradation, resulting that the effective stresses rose during the tests. For that reason, the resilient moduli were normalized to the effective stress, revealing a clear drop on the normalized resilient modulus at a number of cycles depending on the porosity/cement ratio. Notwithstanding, drained and undrained tests presented in this paper performed in uncemented and cemented specimens showed a distinct behavior from granular materials (where the shakedown theory applies) revealing a continuous increase in the accumulated permanent deformations, indicating that long term cyclic triaxial tests, with large number of cycles, may be decisive for a reliable characterization of cyclic triaxial test for bound mixtures.